PRODUCTIVITY OF PURSE SEINE IN MARINE AND FISHERY RESOURCES SUPERVISION BASE (PSDKP) BATAM CITY, RIAU ISLANDS PROVINCE - Isnina Mayang Syafitri; Bustari Bustari; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Batam City based on Regional Regulation Number 2 of 2004 concerning Spatial Planning of Batam City in 2004-2014 is located between 00 25' 29” – 10 15' 00” North Latitude and between 1030 34' 35” – 1040 26' 04” East Longitude. The land area of Batam City reaches 1,038.84 km2 and the water area is 2,791.09 km2 (Batam City Statistics Center, 2018).Management of fisheries resources in Indonesia can be done in various ways, one of which is through fishing business. One of the currently developing fishing techniques is the use of purse seines. In its development,fishing purse seinegear continues to experience improvements, not only in form or construction but also from materials to make boats or ships used for fishing business.Productivity in fishing units has increased and decreased every year, it can be said to have fluctuated. This usually happens because each trip from the GT of the ship to the way of operation is sometimes different. The highest productivity of fishing units onfishing purse seinegear was in 2016 with a total of 255815 kg/GT and the highest CPUE was in 2017 with a total of 14,582 kg/Trip. Vessels operating at PSDKP Batam predominantly have a large GT which ranges from 21 – 198 GT.The factors that affect the productivity ofcatches purse seine are ship size (GT), engine power (PK), fuel consumption (L), net length (m), in net (m), number of crew (persons) and number of lamps (units).